Critical Behaviour of the Ising S=1/2 and S=1 Model on (3,4,6,4) and (3,3,3,3,6) Archimedean Lattices (Communications in Computational Physics, 2011)
We investigate the critical properties of the Ising S=1/2 and S=1 model on(3,4,6,4) and (34,6) Archimedean lattices. The system is studied through the extensiveMonte Carlo simulations. We calculate the critical temperature as well as the criticalpoint exponents γ/ν, β/ν, and ν basing on finite size scaling analysis. The calculatedvalues of the critical temperature for S=1 are kBTC/J=1.590(3), and kBTC/J=2.100(4)for (3,4,6,4) and (34,6) Archimedean lattices, respectively. The critical exponents β/ν,γ/ν, and 1/ν, for S=1 are β/ν=0.180(20), γ/ν=1.46(8), and 1/ν=0.83(5), for (3,4,6,4)and 0.103(8), 1.44(8), and 0.94(5), for (34,6) Archimedean lattices. Obtained resultsdiffer from the Ising S = 1/2 model on (3,4,6,4), (34,6) and square lattice. The evaluatedeffective dimensionality of the system for S =1 are Deff =1.82(4), for (3,4,6,4),and Deff=1.64(5) for (34,6).